A Morphometric Study of Development of Fetus Suprarenal Gland, Kidney and their Comparison - Chandni G,,; Vivek K,,; Sneha Guruprasad K,,; Antony SD’Souza, (Department of Surgery, UKM Medical Centre, 2015)
The suprarenal gland plays a vital role in maintenance of internal milieu. Over the past years, the evaluation of foetal morphometrical growth parameters have been subject of increased awareness for the assessment of foetal growth. In some studies foetal organs were also measured to see their gross development at various gestational ages. So, the aim of our study was to determine the growth rate of foetal suprarenal gland and kidney in increasing gestational age. The present study was carried out in the Department of Anatomy, Kasturba Medical College, Manipal. The material for the study consisted of 30 human foetal specimens from 12th to 28th weeks of gestational ages. The suprarenal glands and kidney were taken from fetal specimens for various measurements. The measurements were done by using calibrated beaker for volume and vernier caliper for linear parameters. Statistical analysis for the measurements was done. At 1-12 weeks there was no significant correlation between kidney and suprarenal gland. At 13-24 weeks there was significant correlation (p <0.05) between weight and length of suprarenal and kidney. At 25- 40 weeks there was significant correlation (as p <0.05) between weight and breadth of suprarenal and kidney. The knowledge of morphometery of the suprarenal gland and kidney is important in cases of anencephaly, hirsutism and hypertension in association with suprarenal cortical and medullary tumors and these measurements may be helpful for the obstetrician because these can give us an indication for finding the gestational age of the fetuses.